2021
DOI: 10.4314/ijs.v22i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Fe , Pb , Zn and Cr ions from aqueous solutions using natural, ammonium oxalate and sodium hydroxide modified Kaolinite clay

Abstract: In this paper, Fe2+ , Pb2+ , Zn2+ and Cr6+ ions removal from contaminated water with natural Nigerian kaolinite clay (AK-clay), and that removed with kaolinite clay modified with either ammonium oxalate (AK-AO) or sodium hydroxide (AK-S) were presented. The clay was characterized using X-Ray Diffractometry (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Brunanuer-EmmettTeller (BET) method. The parameters investigated include pH, adsorbent particle size, shaking spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…These findings correlate with earlier reports of effective adsorption of metal ions at higher pH values where less competition for adsorption sites between [H3O + ] and the positively ions is obtainable (Ozdes et al, 2011, Sari and Tuzen, 2014, and Mohamed et al, 2019. However, the investigation was not extended beyond pH 7 and 4.5 for Ni 2+ as well as Cd 2+ and Pb 2+ respectively because precipitations of the metals were observed beyond these values especially for Pb 2+ ions whose precipitation have been reported to occur from pH 5 (Lawal et al, 2020) while other metals have also been found to occur at higher pH values (Rahmani et al, 2010, Dawodu and Akpomie, 2014, El-Naggar et al, 2019. There have been reports where adsorption of the studied metals increased with increasing pH (Barka et al, 2013, Akpomie and Dawodu, 2014, Krika et al, 2016, El-Naggar et al, 2018, Chai et al, 2020.…”
Section: B Adsorption Studies 1) Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings correlate with earlier reports of effective adsorption of metal ions at higher pH values where less competition for adsorption sites between [H3O + ] and the positively ions is obtainable (Ozdes et al, 2011, Sari and Tuzen, 2014, and Mohamed et al, 2019. However, the investigation was not extended beyond pH 7 and 4.5 for Ni 2+ as well as Cd 2+ and Pb 2+ respectively because precipitations of the metals were observed beyond these values especially for Pb 2+ ions whose precipitation have been reported to occur from pH 5 (Lawal et al, 2020) while other metals have also been found to occur at higher pH values (Rahmani et al, 2010, Dawodu and Akpomie, 2014, El-Naggar et al, 2019. There have been reports where adsorption of the studied metals increased with increasing pH (Barka et al, 2013, Akpomie and Dawodu, 2014, Krika et al, 2016, El-Naggar et al, 2018, Chai et al, 2020.…”
Section: B Adsorption Studies 1) Effect Of Phmentioning
confidence: 99%
“…Modified clays are however not without their own shortcomings, but acid activated clays have been found to provide the most advantages associated with modification. This is due to their ease and low cost of production (Özcan and Özcan, 2004, Mohammed-Azizi et al, 2013, Lawal et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The water at the top layer was decanted and the sedimented clay particles dried in an oven at 105 °C for 1 hour. 36 The following modified procedure was followed to modify SK clay with ammonium carbonate. A 20 g portion of 63 µm fraction of SK clay was added to a 0.5 L solution of 0.2 M ammonium carbonate in a conical flask.…”
Section: Preparation Of Adsorbentsmentioning
confidence: 99%
“…The slurry obtained was centrifuged at 3000 rpm for 30 minutes and the sediment was washed repeatedly with deionised water until a neutral pH was obtained and dried at 105 °C. 36…”
Section: Preparation Of Adsorbentsmentioning
confidence: 99%